Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Pegawai Pada Protokol Sekretariat Daerah Kota Binjai - Berry Nanda Sembiring; Isnaini Isnaini; Dumasari Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study discusses to the development and the factors that hinder the development of human resources in improving employee performance in the Protocol Section of the Binjai City Regional Secretariat. The research method used is descriptive research with a qualitative approach, the data collection instrument is the study of documentation and interviews, while the data analysis used is descriptive analysis. The results of this study indicate that the HR planning carried out by the Protocol Office of the Regional Secretariat of the City of Binjai has been classified as optimal and well, it can be seen that the HR planning through stages in the selection to become members of HR development training and education and HR development training has not been running optimally. Well, it can be seen that there are still people who hold positions but are still not optimal in their implementation so that the purpose of education and training for HR development is only getting a certificate. In terms of human resource management, the Binjai City Regional Secretariat Protocol Service has shown good and effective results. The constraint factors faced in HR development are: the provision of training for employees has not been carried out evenly and communication skills are still lacking, especially communication with leaders.